Pembelajaran Berbasis Kasus (CBL) Dalam Pembelajaran Kimia: Review Sistematik Dari 2011-2021 - Citra Ayu Dewi; Habiddin Habiddin; I Wayan Dasna; Sri Rahayu (Jurnal Penelitian Pendidikan IPA, 2022)
The implementation of Case-Based learning in chemistry learning has grown rapidly in the last ten years. To find trends and issues in the application of case-based learning in chemistry learning, a systematic review is needed. This study aims to analyze the types of CBL and forms of CBL cases used in chemistry learning. The research method used is a systematic review of articles published in the Scopus journal obtained from the Scopus database for the last 10 years (2011-2021). Search articles using titles, abstracts, or keywords that meet logical conditions (â€œCase-Based Learningâ€) or (â€œCase Methodâ€) and (â€œChemistryâ€). The population of this study was 200 articles published in the Scopus database and the sample used was 93 articles. The findings showed that the CBL learning model has a learning syntax that includes four (4) stages, namely: Case Orientation (determining the object to be tested), Peer Instructions (choosing cases that are relevant to the object being studied), Case Review (building initial theory and reviewing literature), Evaluation (collecting, organizing data, analyzing data and developing conclusions). The CBL model presents complex cases in the form of factual news related to the essence of the problem context in the form of story descriptions and integrates information sources in the context to solve cases. The percentages of the 93 articles analyzed were 32% PBI, 31% PBL, and 30% PJBL. Thus, it can be concluded that CBL learning is implemented in three (3) learning approaches, namely CBL in Inquiry-Based Learning, CBL in Problem Based Learning, and CBL in Project-Based Learning